Price regulations and price adjustment dynamics: Evidence from the Austrian retail fuel market - Evanthia Fasoula; Karsten Schweikert (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
After controversial public debates, fuel price regulations were implemented in Austria prohibiting fuel retailers from raising their prices more than once per day. This paper investigates whether these policy measures affected the price transmission dynamics from crude oil prices to retail fuel prices. We estimate different specifications of nonlinear error correction models to quantify a potentially asymmetric adjustment behaviour and compare the results over three subsamples. Particularly, we estimate our models for a pre-regulation period, a between-regulations and a post-regulation period. At first glance, we obtain conflicting results on the efficacy of this policy measure. While the adjustment to the long-run equilibrium seems to be faster if crude oil prices are relatively low, transitory crude oil price decreases are passed through faster than price increases. Only if we consider the combined effect of a crude oil price shock, we can reveal that crude oil price changes are generally passed through faster in the postregulation period. Further, we find that crude oil price decreases are now passed through slightly faster than crude oil price increases. Hence, we conclude that the Austrian fuel price regulation seems to have fostered competition between fuel retailers.
urn:nbn:de:bsz:100-opus-14818
Keywords: C22; D40; Q41; 330; asymmetric price transmission; price regulation; nonlinear error correction model; retail fuel prices; crude oil prices